PERBANDINGAN PERAN MASYARAKATDALAM PENGELOLAAN LIMBAH PADAT ANTARA INDONESIA DAN FILIPINA - Hotimah, Oot; Yantika, Febry; Gita Pertiwi, Gianti (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
Solid waste management is an important issue in many countries, including Indonesia and the Philippines. Both countries have experienced a significant increase in waste volume due to population growth and urbanization. One of the factors contributing to this issue is the low level of public awareness regarding waste segregation for better management. This study aims to compare government policies that serve as the primary benchmark in encouraging community involvement in solid waste management in Indonesia and the Philippines. The research method employed involves the collection of secondary data from journals and the reanalysis of data to obtain new insights. Several proposed solutions include the implementation of the 3R principles (reduce, reuse, recycle) and the development of a solid waste management system focused on waste segregation for reuse and value creation. The results indicate that community participation and a sustainable approach are key factors for successful solid waste management. Such participation motivates other community members to increase their awareness and concern regarding solid waste management.